MENGAPA PERENCANAAN PENDIDIKAN ITU PENTING ? : MENYINGKAP SEJARAH DAN LATAR BELAKANG PENDIDIKAN - Ikas Kasenda; Sukirman Kalam; Edi Zalharis; Kasinyo Harto; Fitri Oviyanti (Irfani (e-Journal), 2025)
Abstract Educational planning is a crucial element in achieving optimal quality of education. This study aims to explain the history and background of the importance of planning in the world of education, as well as the factors that encourage the need for adaptive educational planning that is relevant to the development of the times. Educational planning is not only about formulating goals and strategies, but also includes an understanding of social, economic, political, and technological developments. Over the course of history, educational planning has evolved from being simple in early civilizations to becoming a structured and complex system. Various theories and approaches in educational planning have also changed to adapt to the demands of globalization and technological advances. This article reviews various perspectives from experts and emphasizes the importance of understanding the historical context in designing effective educational planning. Thus, mature educational planning can support the achievement of better educational goals, as well as ensure inclusive and sustainable education in the future. This study also offers suggestions for improving the quality of educational planning to be more responsive to changes and community needs. Keywords: History, Background, Educational Planning